PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. LPPPI - Syamsudin; Adria Wuri Lastari (Fakultas Hukum dan Ekonomi Bisnis, 2024)
The role of management in managing human resources is very influential in organizational development and increasing efficiency and performance productivity in the organization. Human resources are also the main key in an organization. So humans can be seen as a determining factor because in human resources all innovations will be realized in an effort to realize the company's goals. The aim of this research is to determine whether Motivation and Work Environment simultaneously or partially have a significant effect on Employee Performance at the Power Plant at Pt.Lontar Papyrus Pulp And Paper Industry. The population in this study was 48 employees. The sampling technique in this study was probability sampling using a saturated sampling technique, where all samples were taken. The research method uses multiple linear regression analysis methods using the t test, F test and dominant test with a significance level of 5%. The research results and hypothesis show that Motivation and Work Environment simultaneously have a significant effect with the results of multiple linear regression in the F test obtained Fcountof 75.809 is greater than Ftable3.204, while partially using the t test, T was obtainedcountfor each variable, namely Motivation (X1) of 3.876 and Work Environment (X2) of 4.101 which is greater than the T valuetable2.014, then the independent variables, namely the Motivation variable, and the Work Environment influence the dependent variable Employee Performance, while the Work Environment variable has a dominant influence on Employee Performance at Power Plant Pt.Lontar Papyrus Pulp And Paper Industry.